Spatial information system as a tool in managing urban development process - Abdullah, Alias; Noordin, Mohamad Fauzan; Abdullah, Muhammad Faris (2002)
Urban development process is a complex and time-consuming process. Managing it using conventional tools and systems is, without a doubt, a daunting task. Fortunately, the advancement in information technology (IT) has provided the opportunity for urban managers to invent and adopt innovative and effective systems to aid them in performing their tasks. In Malaysia, several local authorities, as the managers of urban development process, has embarked on developing IT-based systems to manage urban development process. Some have achieved considerable success while others were not so fortunate. This paper looks at the problems of paper-based systems in managing urban development process and also identifies some of the weaknesses of the IT-based systems developed by the local authorities for similar purpose. It recommends that a Total Spatial Information System (TSIS) to be developed as a tool to help achieve effective and efficient management of urban development process. It also draws examples from efforts of International Islamic University Malaysia (IIUM) in developing its own TSIS in managing its properties, facilities and assets.